Form Over Substance as Governance Technology: A Mixed-Method Exploration of Performativity in Indonesian Teacher Education - Anita Deka; Dasim Budimansyah; Mupid Hidayat; Momod Abdul Somad (Eduvest - Journal of Universal Studies, 2026)
This research investigates the phenomenon of Form Over Substance (FOS) in Indonesian pre-service teacher education. Drawing on survey data from 347 students and focus group discussions with 15 participants, we inductively developed the Perceived Form Over Substance (PFOS) instrument, an exploratory scale with three dimensions: formalism, image management, and outcome preoccupation. Regression analyses show that systemic pressure for procedural certainty is the strongest predictor of PFOS orientations, outweighing dispositional traits such as the need for social validation. Qualitative findings deepen this picture: students describe ritualized learning, emotional labor in sustaining compliant identities, and grades functioning as social currency under familial surveillance. These patterns suggest that FOS is less a failure of motivation than a systemic outcome of governance regimes that operate through metrics, mimicry, and outsourced compliance. The PFOS instrument offers a preliminary, context-grounded tool for capturing the subjective experience of performative governance. PFOS is not a failure of will but a rational adaptation to systemic pressure, where compliance is not chosen but compelled. Reform requires reconfiguring performative policy technologies, preserving accountability while reducing reliance on forms and metrics, and re-centering teacher education on reflection, substantive evaluation, and meaningful pedagogy.